Left ventricular radial strain impairment precedes hypertrophy in Anderson–Fabry disease - Spinelli, Letizia; Giugliano, Giuseppe; Imbriaco, Massimo; Esposito, Giovanni; Nappi, Carmela; Riccio, Eleonora; Ponsiglione, Andrea; Pisani, Antonio; Cuocolo, Alberto; Trimarco, Bruno (The International Journal of Cardiovascular Imaging, 2020)
In Anderson–Fabry disease (AFD), left ventricular (LV) radial function has been scarcely investigated. We hypothesized that LV function may be affected by disease specific mechanisms and sought to comprehensively evaluate LV radial, circumferential and longitudinal function in a large population of AFD patients looking at the influence of LV geometry and fibrosis. We prospectively studied 94 consecutive AFD patients (41.5 ± 14.5 years; 41 men) with preserved LV ejection fraction (EF) utilizing speckle-tracking echocardiography. A subset of patients underwent gadolinium-enhanced cardiac magnetic resonance. Cases were compared to 48 healthy subjects matched for age and sex. LV concentric hypertrophy was found in 33 AFD patients while LV concentric remodeling (relative wall thickness ≥ 0.43) in 16 out 61 patients with normal LV mass. AFD patients had lower radial, longitudinal and circumferential strains than controls, independently by LV geometry pattern. Patients with LV hypertrophy showed reduced global longitudinal strain (p < 0.001) and early diastolic untwisting rate (p = 0.002) as compared to patients with normal geometry. In the whole AFD population, neither radial strain nor circumferential strain correlated with LV mass, while global longitudinal strain and early diastolic untwisting rate did (both p < 0.001). Late gadolinium enhancement was significantly associated with longitudinal strain, twisting rate and early diastolic untwisting rate, with twisting rate being the most powerful independent predictor (β = − 0.461; p = 0.002). Findings demonstrate impairment of LV radial strain in AFD patients with preserved EF, even in a pre-hypertrophic stage. Development of LV hypertrophy and fibrosis make worse mostly longitudinal dysfunction.